2015
DOI: 10.1136/bmjgast-2015-000052
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D associates with improved quality of life in participants with irritable bowel syndrome: outcomes from a pilot trial

Abstract: BackgroundVitamin D deficiency has been associated or implicated with the pathophysiology of the gastrointestinal conditions inflammatory bowel disease and colorectal cancer, as well as with depression. No trials or epidemiology studies to date have investigated a link with irritable bowel syndrome (IBS). A single case report has suggested a benefit in IBS of vitamin D supplementation. We hypothesised that IBS participants with vitamin D insufficiency would benefit from repletion in terms of their IBS symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 27 publications
0
71
0
1
Order By: Relevance
“…Interestingly, the IBS-C patients in this population were the most responsive to vitamin D supplementation in terms of a striking improvement across nearly all IBS symptoms. 47 Because IBS-C patients are thought to possess lower gut serotonin levels, 48 the responsiveness of these patients to vitamin D supplementation is consistent with the actions of vitamin D to raise gut TPH1/serotonin levels 25 and with our current hypothesis that vitamin D, via induction of the intestinal TPH1 gene, may play a role in IBS pathophysiology. While this study was limited by its small sample size, our IBS cohort displayed a trend toward diminished serum vitamin D levels relative to our non-IBS control group.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Interestingly, the IBS-C patients in this population were the most responsive to vitamin D supplementation in terms of a striking improvement across nearly all IBS symptoms. 47 Because IBS-C patients are thought to possess lower gut serotonin levels, 48 the responsiveness of these patients to vitamin D supplementation is consistent with the actions of vitamin D to raise gut TPH1/serotonin levels 25 and with our current hypothesis that vitamin D, via induction of the intestinal TPH1 gene, may play a role in IBS pathophysiology. While this study was limited by its small sample size, our IBS cohort displayed a trend toward diminished serum vitamin D levels relative to our non-IBS control group.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, the IBS pathological state may be correlated with dysregulated serotonin production, possibly secondary to (or in combination with) vitamin D deficiency. Moreover, during the administration of the current study, another clinical trial was published 47 that reported an IBS cohort with appreciably depressed serum 25(OH)D levels and a significant positive association between quality of life and circulating 25(OH)D concentrations after vitamin D supplementation. Interestingly, the IBS-C patients in this population were the most responsive to vitamin D supplementation in terms of a striking improvement across nearly all IBS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with vitamin D deficiency displayed increased UC clinical disease severity and a lower quality of life (QOL) in a cohort of patients with IBD [14, 15] . After supplementation with recommended doses of vitamin D and reserving saturation of 1,25(OH) D 3 , the serum concentration of vitamin D and health related quality of life can be improved [16, 17] . However, more recently, a study showed that daily supplementation with 1000 IU of vitamin D3, 1200 mg of calcium, or both did not significantly reduce the risk of recurrence of colorectal adenomas after its removal over a period of 3 to 5 years [18] .…”
Section: Vitamin D and Vdrmentioning
confidence: 99%
“…Tazzyman et al (2015) conducted a 12 week randomised double-blind three-arm parallel pilot 12 study in people with IBS which compared placebo to either vitamin D supplementation13 (75µg/d) or combination of vitamin D (75µg/d) plus probiotic (two strains of Lactobacillus 14 acidophilus per capsule). The trial was conducted in the UK in January-April 2015.…”
mentioning
confidence: 99%